2012
DOI: 10.1007/s10620-012-2373-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns and Self-Reported Associations of Diet with Symptoms of Inflammatory Bowel Disease

Abstract: Background There are insufficient data to make firm dietary recommendations for patients with inflammatory bowel disease (IBD). Yet patients frequently report that specific food items influence their symptoms. In this study, we describe patients’ perceptions about the benefits and harms of selected foods and patients’ dietary patterns. Methods CCFA Partners is an ongoing internet-based cohort study of patients with IBD. We used a semi-quantitative food frequency questionnaire to measure dietary consumption p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
202
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(232 citation statements)
references
References 24 publications
15
202
3
4
Order By: Relevance
“…Often leafy or non-leafy vegetables, fruits, dairy, alcohol, red meat or fast food were avoided [12,33]. This is in accordance with our data, since 35% of our patients with IBD stated to have reduced the consumption of fast food compared to only 7% in the healthy control group.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Often leafy or non-leafy vegetables, fruits, dairy, alcohol, red meat or fast food were avoided [12,33]. This is in accordance with our data, since 35% of our patients with IBD stated to have reduced the consumption of fast food compared to only 7% in the healthy control group.…”
Section: Discussionsupporting
confidence: 91%
“…However, several studies showed different effects in patients with IBD on disease course [34], depending on disease type and status [12]. The avoidance of raw fruits and vegetables to reduce gastrointestinal afflictions varied between 8% and 71% [11,33].…”
Section: Food Group Hc Total Ibd Ibd (Intake In [G/d]) CD Ucmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly it is interesting to note the dietary factors implicated in causation of UC in Western studies mentioned above are the predominant food consumed in these countries. But diet definitely affects symptom and course after IBD onset [7][8] .…”
Section: Discussionmentioning
confidence: 99%